Sosialisasi Program Latihan Motor Ablity Kepada Asisten Pelatih Dojo Lembaga Karate-Do Indonesia Se-Kecamatan Koto Tangah - Arie Asnaldi; kibadra Kibadra (Jurnal Berkarya Pengabdian Masyarakat, 2019)
The role of a Dojo trainer in directing karateka to be able to achieve the things mentioned above, the City of Padang has many Dojo including the Dojo Angkasa Lanud Padang. Dojo in the general sense is a training ground. According to Wahid (2007: 8) Dojo which means "a place to study" in Japanese in the past refers to the meaning of "hall to meditate in the temple". Padang Dojo Angkasa Lanud is one of the Dojo Lemkari (Indonesian Karate-DO Institute) which has a Karate shutdown in Padang City, the karateka dojo consists of students from Angkasa Lanud Padang Middle School and the general public. Karateka at the Lemkari Angkasa Lanud Dojo Padang has a variety of achievements where in the past it had had quite a proud achievement that karateka performed in the Kata and kumite categories.